Компьтерный анализ прочности колонн элеватора при различных вариантах нагружения. Часть 1 - Ларин, Алексей Александрович; Трубаев, Александр Иванович; Юдаев, В. В. (Луцький національний технічний університет, 2018)
На основе метода конечных элементов в трехмерной постановке проведен анализ прочности колонн силосов. Расчеты показали, что колонна спроектирована как перегруженная в области капители и работает на пределе кубиковой прочности бетона, хотя по требованиям нормативных документов, которые использовались при ее проектировании, она должна работать в пределах призменной прочности бетона.

Based on the finite element method in a three-dimensional setting, the strength analysis of silo columns was carried out. Calculations showed that the column was designed as overloaded in the base and upper part and works at the limit of cubic strength of concrete, although according to the requirements of the normative documents that were used in its design, it should work within the prismatic compressive strength of concrete. In the upper part of the column, under the action of wind loads, there are significant tensile stresses and there are conditions for the occurrence of a crack. Locations of these sites coincide with the areas where cracks are found during repairs.
Computer analysis of strength of grain elevator columns under various loading options. Part 1
Keywords: силосы; напряженно-деформированное состояние; прочность бетона; зернохранилища; трещины; grain elevator; column; stress-strain state; strength of concrete